2021
DOI: 10.3389/fnut.2021.751405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Galangal Essential Oil Emulsion on Quality Attributes of Cloudy Pineapple Juice

Abstract: Galangal essential oil is obtained from the rhizomes of galangal with proven anti-inflammatory, antioxidant, antiviral, and antimicrobial properties, which are valuable in the food industry. To explore the effect of galangal essential oil on the quality of pineapple juice, 0.05, 0.1, 0.2, and 0.4% galangal essential emulsion were added, and their influence on the physical stability, physicochemical properties, microbial quantity, and aroma profiles of cloudy pineapple juice were evaluated. The essential oil em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…General aspects of essential oils’ physicochemical properties were determined. Color and odor were scored using a scale from 1 to 8; 1 = extremely weak intensity, 2 = very weak intensity, 3 = weak intensity, 4 = moderate intensity, 5 = slight intensity 6 = strong intensity, 7 = very strong intensity, 8 = extremely strong intensity 23 , 24 . pH using a pH meter (HI 9125-Hanna-USA), density according to AFNOR.…”
Section: Methodsmentioning
confidence: 99%
“…General aspects of essential oils’ physicochemical properties were determined. Color and odor were scored using a scale from 1 to 8; 1 = extremely weak intensity, 2 = very weak intensity, 3 = weak intensity, 4 = moderate intensity, 5 = slight intensity 6 = strong intensity, 7 = very strong intensity, 8 = extremely strong intensity 23 , 24 . pH using a pH meter (HI 9125-Hanna-USA), density according to AFNOR.…”
Section: Methodsmentioning
confidence: 99%
“…Decompartmentalisation and bruising of tissue lead to oxidative reactions such as enzymatic browning reaction and consequent generation of dark pigments (González-Aguilar, Ruiz-Cruz, Cruz-Valenzuela, Rodríguez-Félix, & Wang, 2004). Several authors have also reported the beneficial effect of essential oils delaying browning (Çandır, 2017;Nogales-Delgado, 2021;Zhou, Sun, Zou, Zhou, & Liu, 2021). Over time, chroma values of the samples tended to diminish indicating that the colour intensity of pineapple chunks decreased with storage, this tendency being significantly less accused in fruit that was stored in responsive packages.…”
Section: Controlmentioning
confidence: 99%